2021
DOI: 10.1186/s12889-021-10456-x
|View full text |Cite
|
Sign up to set email alerts
|

Health care utilization for patients with stroke: a 3-year cross-sectional study of China’s two urban health insurance schemes across four cities

Abstract: Background Stroke is a devastating disease and a major cause of death and disability in China. While existing studies focused mainly on differences in stroke patients’ health care utilization by insurance type, this study assesses whether health utilization and medical costs differed by insurance type across four cities in China. Methods A 5% random sample from the 2014–2016 China Urban Employees’ Basic Medical Insurance (UEBMI) and Urban Residents… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“… 53 In addition, Beijing has better health care resources, and the diagnosis rate of diseases may be higher than that of other regions. 54 Moreover, with the rapid development of Beijing’s economy, residents’ diets and lifestyles are unique compared with other regions. All of the above may limit the generalizability of these findings.…”
Section: Discussionmentioning
confidence: 99%
“… 53 In addition, Beijing has better health care resources, and the diagnosis rate of diseases may be higher than that of other regions. 54 Moreover, with the rapid development of Beijing’s economy, residents’ diets and lifestyles are unique compared with other regions. All of the above may limit the generalizability of these findings.…”
Section: Discussionmentioning
confidence: 99%
“… 41 NCMS, UEBMI and URBMI were China’s three basic social health insurance schemes, but differed in reimbursement ratios, coverage and contributions. 38 Previous research indicated that medical insurance was associated with the cost and adverse clinical outcomes of stroke, 10 , 42 - 44 therefore, we included the type of insurance in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Thirdly, it was reported that UEBMI beneficiaries demanded more hospital services than they needed, and patients under the UEBMI scheme were more likely to use inpatient services than those covered by the URBMI scheme [ 65 ]. Fourthly, since different therapeutic schedules could be adopted by health providers according to patients’ insurance type, the UEBMI enrollees had a higher percentage of inpatients receiving expensive medications than the URBMI enrollees [ 31 , 66 ]. Therefore, the direct medical costs of patients with PD varied between these two health insurance schemes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the predictors of inpatient costs for patients with PD were selected based on this theoretical framework [ 38 ] and the results of the literature review. Individual influential factors were selected from the following three parts: (1) predisposing characteristics: existing conditions that predispose individuals to health services utilization (such as gender [ 41 , 42 ] and age [ 28 , 30 , 43 , 44 , 45 , 46 , 47 ]); (2) enabling characteristics: conditions that facilitate or impede health services usage (for example, type of insurance [ 31 , 32 ]); (3) need characteristics: conditions that medical providers consider as requiring professional treatment (such as disease subtypes [ 35 , 37 ], hospital levels [ 34 , 48 ], length of stay (LOS) [ 35 , 48 ] and presence of any comorbidities [ 44 , 49 ]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation